Case Report: Localized bullous pemphigoid induced by local triggers: a case series and a proposal for diagnostic criteria based on a literature review - Corbella-Bagot, Lluís; Gil-Lianes, Javier; Fernández-Vela, Javier; Martí-Martí, Ignasi; Alegre-Fernández, Marta; Fuertes, Irene; Garbayo-Salmons, Patricia; Bosch-Amate, Xavier; Guilabert, Antonio; Mascaró, José M. (Frontiers in Immunology, 2023)
Introduction: Localized bullous pemphigoid (LBP) is an infrequent bullous pemphigoid (BP) variant restricted to a body region. According to the most compelling evidence, LBP occurs in patients with pre-existent serum antibodies against the basement membrane zone, which occasionally acquire the capacity to induce disease after the influence of different local factors acting as triggers. Methods: We hereby present a multicenter cohort of 7 patients with LBP developed after local triggers: radiotherapy, thermal burns, surgery, rosacea, edema and a paretic leg. In addition, we conducted a review of the literature, and we proposed a set of diagnostic criteria for LBP based on our case series and the 2022 BP guidelines from the European Academy of Dermatology and Venereology. Results: During follow-up, 3 of the patients from our series evolved to a generalized BP, with only 1 requiring hospitalization. Our literature search retrieved 47 articles including a total of 108 patients with LBP, with a 63% with a potential local precipitating factor previous to their diagnosis. LBP mostly affected older females, and a subsequent generalized progression occurred in 16.7% of the cases. The most frequently involved areas were the lower limbs. Radiation therapy and surgery were responsible for the inducement of nearly 2 in 3 cases of LBP. We observed a significantly higher risk of generalization in cases where the trigger led to the developing of LBP earlier (p=0.016). Our statistical analysis did not detect any other prognosis factor for generalization when assessing direct immunofluorescence, histological and serological results, or other patient related factors. Conclusion: LBP should be suspected in patients with recurrent localized bullous eruptions. The presence of a trauma history in the same anatomic area is reported in most cases.